2005
DOI: 10.3732/ajb.92.11.1911
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny of Flaveria (Asteraceae) and inference of C4 photosynthesis evolution

Abstract: A well-resolved phylogeny of Flaveria is used to infer evolutionary relationships among species, biogeographical distributions, and C(4) photosynthetic evolution. Data on morphology, life history, and DNA sequences (chloroplastic trnL-F, nuclear ITS and ETS) for 21 of 23 known species were collected. Each data set was analyzed separately and in combination using maximum parsimony and Bayesian analyses. The phylogeny of Flaveria is based on the combined analysis of all data. Our phylogenetic evidence indicates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
176
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(186 citation statements)
references
References 57 publications
10
176
0
Order By: Relevance
“…A phylogenetic tree based on the sequences of these eight promoters is in agreement with the phylogeny of the genus Flaveria as proposed by McKown et al (2005) (Figure 6A). The ppcA promoter tree indicates that the ppcA genes of clade A and clade B evolved separately from the ancestral ppcA genes, which resemble the ppcA genes of the present basal C 3 Flaveria species.…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…A phylogenetic tree based on the sequences of these eight promoters is in agreement with the phylogeny of the genus Flaveria as proposed by McKown et al (2005) (Figure 6A). The ppcA promoter tree indicates that the ppcA genes of clade A and clade B evolved separately from the ancestral ppcA genes, which resemble the ppcA genes of the present basal C 3 Flaveria species.…”
Section: Discussionsupporting
confidence: 62%
“…According to the recently published phylogeny of the genus Flaveria, which was based on both morphological and molecular characteristics, all C 4 and C 4 -like species form a distinct clade (clade A), while the C 3 species F. pringlei and F. cronquistii are basal (McKown et al, 2005). The C 3 -C 4 intermediate species of the genus are contained within clade B (McKown et al, 2005).…”
Section: Evolutionary Origin Of Mem1 In the Genus Flaveriamentioning
confidence: 99%
See 2 more Smart Citations
“…Many of these studies (Hermans and Westhoff, 1990;Rajeevan et al, 1991;Rosche et al, 1994;Marshall et al, 1996;Drincovich et al, 1998;Lai et al, 2002) used members of the genus Flaveria as model organisms for understanding the steps involved in the evolution of C 4 photosynthesis, because this group of closely related plants contains individual species demonstrating C 3 , C 4 , or intermediate C 3 -C 4 photosynthesis, indicating that the evolution toward C 4 photosynthesis is ongoing in this genus (McKown et al, 2005). The results from several of these studies demonstrated that the genes encoding the enzymes important in C 4 photosynthesis evolved through the duplication of ancestral C 3 genes followed by the neofunctionalization of one copy, which involved increased gene expression in specific organs and cell types (for review, see Monson, 2003).…”
mentioning
confidence: 99%